Hipertensi pada Lansia: Faktor Risiko dan Strategi Upaya Pencegahan (Literature Riview) - Miftahurrahmah El Hayatli; Tiara Khairani Br Purba; Lilya Yulandari; Abid Farhan; Nadia Aulia Putri Nasution (CV. ITTC INDONESIA, 2026)
Hypertension in older adults is a global health problem whose prevalence continues to rise with the aging process and is a leading cause of cardiovascular complications such as stroke, coronary heart disease, and kidney failure. In Indonesia, the burden of hypertension among the elderly remains high while health service coverage stays low, and the implementation of control policies at the community level still faces various obstacles. This article aims to examine the risk factors of hypertension in older adults and to formulate evidence-based prevention strategies through a literature review approach. The method used was a literature review of fifteen relevant national scientific articles, covering quantitative, qualitative, and literature review studies published in recent years. The results show that risk factors for hypertension in older adults include non-modifiable factors such as age, sex, and genetics, as well as modifiable factors such as a high-salt diet, obesity, lack of physical activity, and stress. Effective prevention strategies include health education based on the CERDIK program, family support empowerment, proactive door-to-door screening, local food innovation such as papaya pudding, and training in independent blood pressure monitoring at home. The combination of these strategies has been shown to improve the knowledge, adherence, and quality of life of older adults with hypertension. This study recommends that health policymakers adopt a multidimensional intervention model that combines education, family empowerment, active screening, and nutritional innovation to reduce the incidence of hypertension among older adults in Indonesia.